(untitled) (European Journal of Interdisciplinary Research and Development, 2024)
This article discusses the importance of films in learning English, their psychological, socio-cultural, pedagogical, paralinguistic and linguistic features in the formation of language skills. This article also provides recommendations on choosing the right film for language learning.